Workaholism and Marital Satisfaction Among Female Professionals. (October 2015) - Levy, Daniele V.
Workaholism is a modern construct pertaining to how one relates to work pursuits. It has been commonly operationalized as excessive work involvement, driven by internal compulsions, and accompanied by low professional enjoyment. This study evaluated the effect of Spence and Robbins' workaholism triad on marital satisfaction among professional women. Self-report measures were collected online from 266 married alumnae from top graduate schools of business currently in the U.S. labor force. Workaholism components were found to explain a significant amount of variance in marital satisfaction with lack of work enjoyment and high work involvement related to low marital satisfaction. Drive did not exert a significant effect. Results demonstrate that workaholic behaviors and attitudes are associated with poorer marital functioning in this population.